2020
DOI: 10.1002/pra2.278
|View full text |Cite
|
Sign up to set email alerts
|

Understanding users' accessing behaviors to local Open Government Data via transaction log analysis

Abstract: The rapid development of Open Government Data (OGD) and the increasing attention on data use/reuse have stimulated many studies on data‐related issues. However, the findability of OGD is still one of the major challenges. Aiming to ameliorate the situation that “data is hard to find”, this paper examines OGD users' needs and accessing behaviors when interacting with local OGD portals. Transaction log analysis and web content mining were used in order to obtain insights from large groups of OGD users in an unob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…A channel indicates a source or manner that assists people in finding the OGD portal's website. We found that OGD users use various channels to access OGD portals (e.g., P12, P14), such as search engines and referrals, aligning with previous work (Koesten et al, 2019; Xiao et al, 2020). By utilizing these channels, users can easily find the OGD portal's website and gain access to the information it contains.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…A channel indicates a source or manner that assists people in finding the OGD portal's website. We found that OGD users use various channels to access OGD portals (e.g., P12, P14), such as search engines and referrals, aligning with previous work (Koesten et al, 2019; Xiao et al, 2020). By utilizing these channels, users can easily find the OGD portal's website and gain access to the information it contains.…”
Section: Resultssupporting
confidence: 89%
“…Search & Browse are the two main search strategies people use to seek data (Xiao et al, 2020). Search refers to a keyword search strategy in which individuals enter search queries into OGD portals.…”
Section: The Initial Conceptual Model For Human Ogd Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants in the LoDL faced different challenges at the concrete experience stage. When seeking data, this group was more likely to use a browsing approach, which, while common among OD users (Xiao et al , 2020), was ineffective. Due to limited knowledge of how data are structured and methods to handle data, tooltips may not be enough to help inexperienced data users, who may benefit more from walk-through tutorials or wizards that scaffold procedural knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were asked to find an appropriate data set and research the salaries for two occupations, one defined (Librarian) and one of their own choosing, on behalf of a friend and to write up their findings using an email template. Salary data is a common OD search topic (Xiao et al, 2020), and the task scenario focused on career planning, a life-task of relevance to university student Learning opportunities for students participants, to increase validity and participant engagement (Borlund, 2003;Kelly, 2009). Study tasks required the use of one of three salary-related data sets among the 160 data sets available through the portal: the Employee and Remuneration and Expenses Earning over $75,000 (ERE-75K) data set.…”
Section: Assigned Tasksmentioning
confidence: 99%